Odour cues from suitors’ nests determine mating success in a fish - Lehtonen, Topi K. (Biol Lett, 2015)
Animals use a range of sensory cues for finding food, avoiding predators and choosing mates. In this regard, the aquatic environment is particularly suitable for the use of olfactory and other chemical cues. Nevertheless, mate choice research, even on aquatic organisms, has focused on visual signals, while chemical cues relevant in sexual selection have been assumed to be ‘intrinsic’ excretions of mate candidates. Here, using the sand goby Pomatoschistus minutus, a small fish with paternal egg care, we investigated the possibility that ‘extrinsic’ chemical cues in the males’ nests could also have a significant contribution to mating success. We found that females strongly avoided laying eggs into nests subject to the odour of Saprolegnia water moulds (an egg infection) and that this effect was independent of the females’ initial, visually based preference for males. To the best of our knowledge, this is the first study to show that chemical cues related to parental failure can play a large role in sexual selection.